Fostering Directly Observed Treatment in Tuberculosis: A Program Manager's Perspective - Saurabh Shrivastava; Prateek Shrivastava; Jegadeesh Ramasamy (Kerman University of Medical Sciences, 2014)
Global Tuberculosis (TB) report (2013) has revealed that an estimated 8.6 million people developed TB of which, India accounts for almost 26% of the cases. These estimates clearly suggest that the country's efforts to achieve Millennium Development Goal 6 by 2015 have not delivered the desired output. In India, the TB prevention and control activities are supervised and implemented under the Revised National TB Control Program (RNTCP), which recognizes that implementation of a good quality Directly Observed Treatment with Short course chemotherapy (DOTS) is the first priority for TB control. Directly Observed Treatment (DOT) is the key element in DOTS strategy, in which a DOT provider insures and supports the patients in consuming their drugs throughout the course of treatment. In order to meet the country's vision to achieve universal access of TB care, the RNTCP has launched a "treatment adherence scheme" (public-private partnership scheme). Further, an evidence-based integrated strategy should be formulated for addressing the identified barriers which advocates universal administration of DOT. To conclude, DOT in RNTCP insures long-term adherence to the treatment, with right drugs in right doses, at right intervals and thus plays an indispensable role in improving the outcome indicators of the program and the quality of life in patients.